Setting the Stage for Dissension: Revival in Northampton, Massachusetts and the Dismissal of Jonathan Edwards - Coté, Zachary (CSUCI Journal of Undergraduate Research, 2013)
The dismissal of Jonathan Edwards is crucial to understanding colonial history and society. Understanding the religious dynamics of Northampton during his tenure provides insight into the evolving structure of New England society only a generation before the American Revolution. Also, viewing the differences in church doctrine between the Connecticut River Valley Revivals, in where Edwards emphasized justification by faith alone, and the Great Awakening, which stressed an emotional experience and a distrust for the traditional church authority of ministers, indicates ways that religion altered how Edwards’ congregation perceived their pastor and their faith.